PENGARUH MANAGEMENT CHANGE, FINANCIAL DISTRESS, UKURAN PERUSAHAAN KLIEN, DAN OPINI AUDIT TERHADAP AUDITOR SWITCHING - Nurul Aini; M. Rizal Yahya (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The research examines the effect of management change, financial distress, client’s size, and audit opinion on auditor switching. The population in this research are the banking companies listed in Indonesia Stock Exchange for year of 2010-2015. The samples in this study using purposive sampling method, the number of obsevations of a sample of 84 studies. The data analysis technique used is logistic regression analysis.The result of this reasearch show that management change, financial distress, client’s size and opinion audit have effect on auditor switching. Partially the research show that (1) Management change significantly influences on auditor switching, (2) financial distress do not affects on auditor switching, (3) client’s size significantly influences on auditor switching, and (3) audit opinion significantly infleunces on auditor switching.